Erratum to: Titanium scaffold osteogenesis in healthy and osteoporotic rats is improved by the use of low-level laser therapy (GaAlAs) (Lasers Med Sci, (2016), 31, (899-905), 10.1007/s10103-016-1930-y) - de Vasconcellos, Luana Marotta Reis [UNESP]; Barbara, Mary Anne Moreira [UNESP]; da Silva Rovai, Emanuel; de Oliveira França, Mariana [UNESP]; Ebrahim, Zahra Fernandes [UNESP]; de Vasconcellos, Luis Gustavo Oliveira [UNESP]; Porto, Camila Deco [UNESP]; Cairo, Carlos Alberto Alves (Springer Nature, 2017)
The published online version of the paper contains a mistake on how the author name was captured. Emanuel da Silva Rovai should be cited as Rovai, E.S., where particle Bda^ will now be part of the given name. The correct citation is shown below: de Vasconcellos, L.M.R., Barbara, M.A.M., Rovai, E.S. et al. Lasers Med Sci (2016) 31: 899.